Workplace Stress and Work-Family Conflict: Employee Perception towards Job Performance / Izmayani Sa'adin, Prof. Madya Dr. Amran Awang and Prof. Madya Dr. Husna Johari - Sa'adin, Izmayani; Awang, Amran (Prof. Madya Dr.); Johari, Husna (Prof. Madya Dr.) (2012)
The objective of research in general is to identify the relationship between workplace stress and work-family conflict toward job performance of employees. In gathering data, the questionnaire based on previous study conducted by Maimunah and Asmah (1990), Baskaran (2004), Netemeyer (1996) and Usha (1999) has been used. Job performance was measured by adopting the general scheme provided by Maimunah and Asmah (1990). The data was collected from 191 respondents by using a structured questionnaire. Three main hypotheses were tested using multiple regression analysis. Results of the study indicate that there is a significant relationships between workplace stress and job performance (beta value = .477, p .000 - significant relationship). Result also found that there is no relationship between work family conflict toward job performance (beta value = .584, p .003). From the finding, workplace stress was identified as a main factor that affects job performance of the employees especially those working in financial industry. 12.5% of the variance has been significantly explained by workplace stress. The findings support past evidence that workplace stress and work-family conflict are significant factor that affect job performance among employees